Light as a Broad-Spectrum Antimicrobial - Gwynne, Peter J.; Gallagher, Maurice P. (Frontiers in Microbiology, 2018)
Antimicrobial resistance is a significant and growing concern. To continue to treat even simple infections, there is a pressing need for new alternative and complementary approaches to antimicrobial therapy. One possible addition to the current range of treatments is the use of narrow wavelength light as an antimicrobial, which has been shown to eliminate a range of common pathogens. Much progress has already been made with blue light but the potential of other regions of the electromagnetic spectrum is largely unexplored. In order that the approach can be fully and most effectively realised, further research is also required into the effects of energy dose, the harmful and beneficial impact of light on eukaryotic tissues, and the role of oxygen in eliciting microbial toxicity. These and other topics are discussed within this perspective.